Evolution of climate, glaciation and subglacial environments of Antarctica from the deep ice core and Lake Vostok water sample studies (Key results of implementation of the Russian Science Foundation project, 2014–2016) - V. Ya. Lipenkov; A. A. Ekaykin; I. A. Alekhina; Yu. A. Shibaev; A. V. Kozachek; D. O. Vladimirova; N. I. Vasilev; A. V. Preobrazhenskaya (Лëд и снег)
Work on the project focused on the following five areas: 1)  field works in Antarctica at Vostok and Concordia stations; 2)  experimental and theoretical studies in the field of ice core and paleoclimate research; 3) experimental and theoretical works related to the exploration of subglacial Lake Vostok; 4) development of technology and drilling equipment for deep ice coring and exploration of subglacial lakes; 5) upgrading the analytical instrumentation in the Climate and Environmental Research Laboratory (CERL) of the Arctic and Antarctic Research Institute. The main achievements in the field of ice core and paleoclimate research include 1) further elaboration of a new method of ice core dating, which is based on the link between air content of ice and local insolation, 2) investigation of the possible applications of the 17O-excess measurements in ice core to the paleoclimate research, 3)  a better understanding of the mechanisms of the formation of relief-related variations in the isotopic content of an ice core drilled in the area of Antarctic megadunes, and 4) obtaining the first reliable data set on the variations of the 17O-excess in the Vostok core corresponding to marine isotope stage 11. As part of our studies of subglacial Lake Vostok, we have obtained a large body of new experimental data from the new ice core recovered from the 5G-3 borehole to the surface of the subglacial lake. Stacked profiles of isotopic composition, gas content and the size and orientation of the ice crystals in the lake ice have been composed from the data of three replicate cores from boreholes 5G-1, 5G-2 and 5G-3. The study reveals that the concentration of gases in the lake water beneath Vostok is unexpectedly low. A clear signature of the melt water in the surface layer of the lake, which is subject to refreezing on the icy ceiling of Lake Vostok, has been discerned in the three different properties of the accreted ice (the ice texture, the isotopic and gas content of the ice). These sets of data indicate in concert that poor mixing of the melt (and hydrothermal) water with the resident lake water and pronounced spatial and/or temporal variability of local hydrological conditions are likely to be the characteristics of the southern end of the lake. A considerable part of the funding allocated by the RSF to this project was used for upgrading the analytical instrumentation for ice core studies in the CERL of AARI. Using this grant, we purchased and started working with the Picarro L-2140i, a new-generation laser mass analyzer, and set the upgraded mass spectrometer Delta V Plus into operation. The new equipment was used to carry out research planned as part of the project, including the setting up and carrying out of new measurements of 17О in ice cores.